Sem título : um quadro de uma possível produção criativa - Martins, Ana Claudia Sampaio (2020)
The present thesis is inserted in the studies of Creative Writing, it was produced in two equally important parts. The first consists of a novel and the second is a theoretical essay. The novel has as its theme the relationship between painting and curatorship, this theme appears through the conflict of the main character Greta, she is a painter and curator of a private gallery, however, she has difficulties in understanding herself as an artist. This is the guiding thread of the narrative, which develops its plot in line with the protagonist's internal conflict. The fictional text has two narrators - one in the first person, narrated by the main character Greta and the other in the third person, through an omniscient narrator. Both narrators provoke the traditional instances of the narrative. That said, the theoretical essay seeks to problematize the themes addressed in the fictional text, such as the presence of the two narrators, the status of painting in contemporary art, the role of the curator in the art world and, finally, the identity acceptance of the protagonist. The two parts of the thesis seek to ally themselves as a way of drawing an overview of the creative processes in which a literary text travels.